PENGARUH SUPERVISI KEPALA SEKOLAH DAN KOMUNIKASI ANTAR PRIBADI TERHADAP KEPUASAN KERJA GURU SD NEGERI SE- KECAMATAN LIMA KAUM - Rian Yohanas (IAIN Batusangkar, 2018)
This study aims to determine: (1) principal supervision of teacher work satisfaction; (2) interpersonal communication of teacher work satisfaction; and (3) principal supervision and interpersonal communication of teacher work satisfaction. This research is expost facto that is research which aims to know influence of a variable to other variables. The population of this research is Elementary school teachers in Lima Kaum District as many as 153 people. The sampling using probability sampling technique, so the sample amounted to 60 people. The data collection is questionnaires and documentation. Testing the instrument with validity and reliability test. Data analysis techniques use descriptive statistics and inferential statistics with prerequisite analysis test using normality test, homogeneity test, linearity test, multicollinearity test and autocorrelation test. The hypothesis test using partial test (t test) and simultaneous test (F test). The results are: (1) principal supervision did not affect of teacher job satisfaction; (2) interpersonal communication influenced of teacher work satisfaction; and (3) principal supervision and interpersonal communication (X2) together towards teacher work satisfaction. If the principal supervision is done well and interpersonal communication is done effectively will have a positive effect on the improvement of teacher work satisfaction.